The Influence of Internal and External Stakeholder Mechanisms on Entrepreneurial Success: The Moderating Role of Digital Technology Adoption - Yong, Cui; Firdousi, Saba Fazal; Afzal, Ayesha; Florjančič, Viktorija; Awais, Minahil (Frontiers in Psychology, 2022)
The purpose of this research is to investigate the associations of internal and external support mechanisms with entrepreneurial success, in the context of China's entrepreneurial sector from network theory perspective. The role of digital technology, as a moderator, has also been analyzed. Data has been obtained from 500 entrepreneurs in Jiangsu, a province in China. All hypotheses were tested using structural equation modeling. It has been found that family support, business partner support, community support and external stakeholder relationships have positive effects on entrepreneurial success. It has also been discovered that digital technology adoption strengthens the positive relationship between business partner support and entrepreneurial success. Theoretical and practical implications have been highlighted and future research suggestions have been provided.